Moodle in Arabic Learning: How It Works at SMK Syafi’i Akrom Pekalongan - Jauhar Ali (ALSINATUNA, 2019)
This study aims to describe and analyze deeply the use of Moodle's open source e-learning at Syafi'i Akrom Pekalongan Vocational School. This is a kind of field research and the process of collecting the data uses observation, interviews and documentation techniques. Data analysis was conducted using analytical description and comparative method (Constant Comparative Method) techniques. The results showed: (1) Moodle-based e-learning at Syafi'i Akrom vocational school has not been utilized properly and optimally by all teachers and only IT teachers knowing how to use it; (2) Moodle-based Arabic E-learning at Syafi'i Akrom Vocational School also has not been utilized properly and optimally in Arabic learning process. It still uses conventional methods and media by having face to face meeting with the provided media; (3) The aim and objective of e-learning at Syafi'i Akrom Pekalongan Vocational School is realizing the media as one of the alternative media in learning to create more independent learning process without problems of place and time. Besides, the teacher has more flexible time due to the Internship Program for the XI graders; (4) The supporting factors of Arabic e-learning in Syafii Akrom vocational school are sufficiently complete facilities, the existence of elearning.ponpes-smksa.sch.id as the e-learning website, sufficient funding support, IT training, and student ability in the use of ICT. The obstacles of the e-learning in this vocational school is the lack of ability and interest of teachers in using IT that enables the lack of ability to provide more interactive material for the students, the complexity of the features in Moodle, and the students’ who come from non Madrasa / Islamic boarding school backgrounds which have low ability in understanding Arabic.